Improvements in α-Amylase Immobilization Techniques for Corn Starch Hydrolysis: Performance, Stability, and Applications - Tafahn, Randy; Ardelia Fidela Sharfina (Journal of Biobased Chemicals, 2026)
This review provides a comprehensive overview of α-amylase immobilization techniques developed between 2016 and 2026, offering a quantitative basis for selecting appropriate methods for industrial starch hydrolysis. The immobilization of α-amylase is a key strategy to address the limitations of free enzymes in starch hydrolysis, particularly for corn starch, by enhancing thermal stability, pH tolerance, and reusability. Commonly used immobilization methods include physical adsorption, entrapment, covalent bonding, and cross-linking of enzyme aggregates. Recent developments also include the use of nanocomposite materials such as chitosan, bentonite, magnetic nanoparticles, metal-organic frameworks (MOFs), and layered double hydroxides (LDHs) as supports. Comparative studies of 38 selected original research articles indicate that each method has advantages and limitations in catalytic activity, stability, mass-transfer efficiency, and reusability. Covalent bonding on magnetic nanomaterials provides the best operational stability, with many systems achieving reuse over 10 cycles (up to 20 cycles in magnetic-chitosan and MOF-based systems). At the same time, bimetallic core-shell nanoparticles shift the optimum temperature to 80 °C. Entrapment in alginate or gellan hydrogels offers high reusability (up to 20 cycles) but may suffer from diffusion limitations. Cross-linked enzyme aggregates, with starch as a protective agent, retain > 65% of their activity after 25 cycles. Hybrid methods that combine magnetic separation with biodegradable polymers (e.g., polycaprolactone) represent an emerging direction in sustainable biocatalyst design. Future research should focus on the design of multifunctional hybrid biocatalysts that can be economically applied in industry while addressing the technical challenges of mass transfer and the consistency of supporting material quality.